1998
DOI: 10.1021/cm970704g
|View full text |Cite
|
Sign up to set email alerts
|

Dihexylquaterthiophene, A Two-Dimensional Liquid Crystal-like Organic Semiconductor with High Transport Properties

Abstract: End-substitution of quaterthiophene with hexyl groups leads to a highly soluble conjugated oligomer, α,ω-dihexylquaterthiophene (DH4T), which has been characterized for its thermal, structural, and electrical properties. Differential scanning calorimetry indicates the existence of a 3-dimension (3D)-to-mesophase transition, occurring at 84 °C, below the melting temperature of the material (179 °C). X-ray diffraction patterns performed on crude and thermally treated films of DH4T confirm the existence of a smec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
121
3
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(130 citation statements)
references
References 17 publications
5
121
3
1
Order By: Relevance
“…19,20 The Phillips research group then studied thienylethynyl-terthiophene derivatives as liquid crystalline organic semiconductors and succeeded in fabricating single-domain crystalline OFETs by a phase transition from a nematic phase on an alignment layer, 21 whereas Funahashi et al 22 reported the FET performance in the liquid crystalline phase of a phenyl-terthiophene derivative (3-TTP-Ph-5). The FET mobility of these FETs was up to 10 − 2 cm 2 Vs − 1 .…”
Section: Liquid Crystals As Ofet Materialsmentioning
confidence: 99%
“…19,20 The Phillips research group then studied thienylethynyl-terthiophene derivatives as liquid crystalline organic semiconductors and succeeded in fabricating single-domain crystalline OFETs by a phase transition from a nematic phase on an alignment layer, 21 whereas Funahashi et al 22 reported the FET performance in the liquid crystalline phase of a phenyl-terthiophene derivative (3-TTP-Ph-5). The FET mobility of these FETs was up to 10 − 2 cm 2 Vs − 1 .…”
Section: Liquid Crystals As Ofet Materialsmentioning
confidence: 99%
“…Excited states of thiophene attracted particular attention as this molecule constitutes the smallest building block of oligo and polythiophenes-materials extensively used in organic electronics [16][17][18][19][20]. In consequence, the energetics and electronic structure of thiophene are quite firmly established.…”
Section: Introductionmentioning
confidence: 99%
“…[4] A number of elegant micro-actuators have been constructed as bilayers where the difference between the expansion of two conducting polymers or a conducting polymer layer and a metallic support results in a bending movement. [5,6] This strategy is less practical for larger scale actuation because the resulting force is low, and because it is difficult to constrict the bending to one dimension only with large-area polymer films. An alternative is to develop linear actuators, where the length change of a conjugated polymer strip is used directly as the actuating element.…”
mentioning
confidence: 99%